From Cádiz to La Liga the Spanish Context of Rizal’s political thought. - Aseniero, George (2013)
José Rizal wrote his major works in the 1880s but the prevailing viewin Rizal scholarship today is that philosophically, his worldview was firmly rooted in the French Enlightenment; how then could the theories of the preceding century serve him in confronting the issues of the 19th century, so radically different from those that brought an end to the ancien régime
everywhere? Most commentators say his limited exposure to 19th-century political economy–evidenced by the absence in his library of the major works of the period, coupled with the limitations of his class, being of the ilustrado elite and distant from the toiling masses–prevented him from understanding fully the contradictions of his time; hence his politics of reformism and his rejection of revolutionary practice. Taking a contrary stance, this essay seeks to understand Rizal’s political thought in relation to the great political struggles of Spain, from the 1812 Cádiz Constitution of the original ilustrados, through the 1868 Glorious Revolution of the liberals, down to the aborted Spanish Republic of 1873/74 of the republicans, foremost of whom was the socialist-republican Francesc Pi y Margall, Rizal’s intellectual mentor, political ally, and personal friend. A reading of Rizal’s major essays in the on text of Spain’s constitutional struggles–the politics of transformation versus the politics for conservatism–and the revolutionary vision of Pi y Margall reveals the logic of his emancipatory discourse and displays the groundings of his political economic program of La liga Filipina firmly in early 19th-century mutualist traditions of the European Left.
Keywords: Rizal, Jose ,1861-1896; Cadiz constitution; Pi y Margall; La Liga Filipina